Alternate approach to assembly stack analysis and process tolerancing of parts - Cheong, Khin Cheong. (2008)
This project furthered the work in the field of process tolerance charting as well as improve the method of tolerance stack analysis for assemblies. A single relational chart concept is suggested in this report which aids in defining the working dimension and working tolerance equations for each of the process stips involved in the manufacturing of a typical component.